Male gender is a predictor of higher mortality in hospitalized adults with COVID-19 - Nguyen, Ninh T.; Chinn, Justine; De Ferrante, Morgan; Kirby, Katharine A.; Hohmann, Samuel F.; Amin, Alpesh (PLOS ONE, 2021)
Introduction The coronavirus disease 2019 (COVID-19) pandemic continues to be a global threat, with tremendous resources invested into identifying risk factors for severe COVID-19 illness. The objective of this study was to analyze the characteristics and outcomes of male compared to female adults with COVID-19 who required hospitalization within US academic centers. Methods Using the Vizient clinical database, discharge records of adults with a diagnosis of COVID-19 between March 1, 2020 and November 30, 2020 were reviewed. Outcome measures included demographics, characteristics, length of hospital stay, rate of respiratory intubation and mechanical ventilation, and rate of in-hospital mortality of male vs female according to age, race/ethnicity, and presence of preexisting comorbidities. Results Among adults with COVID-19, 161,206 were male while 146,804 were female. Adult males with COVID-19 were more likely to have hypertension (62.1% vs 59.6%, p <0.001%), diabetes (39.2% vs 36.0%, p <0.001%), renal failure (22.3% vs 18.1%, p <0.001%), congestive heart failure (15.3% vs 14.6%, p <0.001%), and liver disease (5.9% vs 4.5%, p <0.001%). Adult females with COVID-19 were more likely to be obese (32.3% vs 25.7%, p<0.001) and have chronic pulmonary disease (23.7% vs 18.1%, p <0.001). Gender was significantly different among races (p<0.001), and there was a lower proportion of males versus females in African American patients with COVID-19. Comparison in outcomes of male vs. female adults with COVID-19 is depicted in Table 2. Compared to females, males with COVID-19 had a higher rate of in-hospital mortality (13.8% vs 10.2%, respectively, p <0.001); a higher rate of respiratory intubation (21.4% vs 14.6%, p <0.001); and a longer length of hospital stay (9.5 ± 12.5 days vs. 7.8 ± 9.8 days, p<0.001). In-hospital mortality analyzed according to age groups, race/ethnicity, payers, and presence of preexisting comorbidities consistently showed higher death rate among males compared to females (Table 2). Adult males with COVID-19 were associated with higher odds of mortality compared to their female counterparts across all age groups, with the effect being most pronounced in the 18–30 age group (OR, 3.02 [95% CI, 2.41–3.78]). Conclusion This large analysis of 308,010 COVID-19 adults hospitalized at US academic centers showed that males have a higher rate of respiratory intubation and longer length of hospital stay compared to females and have a higher death rate even when compared across age groups, race/ethnicity, payers, and comorbidity.